Highly Robust Rhenium(I) Bipyridyl Complexes Containing Dipyrromethene‐BF2 Chromophores for Visible Light‐Driven CO2 Reduction. Issue 14 (17th May 2022) - Qiu, Li‐Qi; Yang, Zhi‐Wen; Yao, Xiangyang; Li, Xiao‐Yang; He, Liang‐Nian
Abstract: New rhenium bipyridyl complexes with dipyrromethene‐BF2 chromophores (A‐ReBDP‐CZ, A‐ReBDP2, ReBDP‐CZ, and ReBDP2 ) were developed for highly efficient photocatalytic carbon dioxide (CO2 ) reduction to carbon monoxide (CO). These catalysts consisted of two moderate electron‐deficient groups (dipyrromethene‐BF2, BDP) as the visible‐light‐harvesting antenna as well as both electron donor ( N ‐phenylcarbazole, CZ) and acceptor (BDP) on Re bipyridyl framework. Among ReBDP‐CZ and ReBDP2 complexes, the ReBDP2 incorporating two electron‐deficient BDP chromophores had a longer‐lived photoexcited state (182.4 μs) and a twofold enhanced molar absorption coefficient ( ϵ =157000 m −1  cm −1 ) compared with ReBDP‐CZ. Thus, ReBDP2 achieved the superior photocatalytic reactivity and stability with a CO turnover number (TONCO ) value as high as 1323 and quantum yield ( Φ CO ) up to 55 %, which was the most excellent photocatalysis efficiency among the single‐active‐site Re catalysts without additional photosensitizer. Furthermore, the acetylene‐bridged linker was detrimental to the photoactivity and durability of the catalyst. In brief, two BDP‐based Re bipyridyl systems with outstanding catalytic performance and significant visible‐light‐harvesting capabilities in the solar spectrum offer a promising strategy for solar‐to‐fuel conversion schemes. Abstract : CO2 photoreduction : Toward building robust artificial photosynthetic systems, a series of single‐active‐site rhenium bipyridyl complexes with dipyrromethene‐BF2 units exhibit outstanding catalytic efficiency for visible light‐driven‐CO2 reduction.